IMRT and HDR-ICBT for Locally Advanced Clear Cell Adenocarcinoma of the Cervix in Uterus Didelphys Associated With Unilateral Renal Agenesis - Lei, Chengzhi; Huang, Manni; Li, Ning; An, Jusheng; Xiong, Suiyang; Li, Xiaoguang; Wu, Lingying (Frontiers in Oncology, 2020)
Clear cell adenocarcinoma of the cervix (CCAC) with genitourinary malformations is rare. Here, we report a case of CCAC in uterus didelphys (UD) associated with unilateral renal agenesis (URA) that was treated with intensity-modulated radiotherapy (IMRT) and high-dose rate intracavitary brachytherapy (HDR-ICBT). We also retrospectively reviewed the medical records of CCAC cases with genitourinary malformations treated at the National Cancer Center/Cancer Hospital (Beijing, China) between December 2006 and June 2017. Eight cases of this rare condition were identified by pathologic diagnosis. Seven patients received surgical treatment including radical hysterectomy (n = 4), modified radical hysterectomy (n = 1), and total hysterectomy (n = 2). Five patients received adjuvant radiotherapy and chemotherapy after surgery. One patient with CCAC in UD associated with URA was treated with radical IMRT and adjuvant chemotherapy. The eight patients were followed up for an average of 7.9 years; in seven cases, there was no evidence of disease recurrence, while one patient relapsed and died after 1.5 years of treatment. On the basis of these findings, locally advanced CCAC in UD associated with URA can be effectively treated with radical IMRT.